“DESA WISATA” BERBASIS PENGALAMAN SEBAGAI USAHA SOSIAL - Parikesit, Bonifasius Santiko; Suprayogi, Suprayogi; Yudithadewi, Dien (PT Naureen Digital Education, 2023)
This study aimed to provide a new perspective on the development of an experiential tourism village as a social enterprise, which was carried out through the collaboration of the Corporate Social Responsibility (CSR) program of PT Perusahaan Gas Negara Tbk and the community of Lance Island, which located in Kelurahan Tembesi, Kecamatan Sagulung, Batam City. The social enterprise-based concept was encouraged to create community-based business opportunities, in order to overcome the challenges around them, while improving economic, social and environmental capabilities. The research used a qualitative method, where the data collection process was conducted through in-depth interviews with relevant stakeholders, consisting of: (1) social enterprise representatives: three people, (2) community representatives: two people, (3) government representatives: two people, (4) Community Development team from the company: two people, and (5) mentoring partners: two people. The interview process was conducted throughout April 2023. To enrich the process, researchers also conducted a literature review consisting of journals, official government and organization websites, also online media. The analysis showed that there were positive impacts created by the collaboration program for the development of experiential “tourism village” in terms of society, well-being, and economy. However, the nature aspect still requires further exploration.